International tourists purchase intention towards low-carbon tour packages / Teng-Yuan Hsiao, Pei-Ling Sung and Chia-Yun Lu - Hsiao, Teng-Yuan; Sung, Pei-Ling; Lu, Chia-Yun (UiTM Press, 2017)
More attention hence has been paid to low-carbon economic theory to reduce carbon dioxide emissions and understand green development. Therefore, the concept of low-carbon tourism has become increasingly accepted. Also, travel agencies play a crucial role in promoting the concept of environmental protection and low-carbon tourism. In recent years, the importance of the tourism development has been emphasized in Taiwan. The government has developed various tourist policies, and the number of tourists in Taiwan has increased to more than 10 million in 2015. However, no studies have investigated the international tourists in Taiwan who purchased low-carbon tour packages provided by travel agencies. The present study, therefore, explored international tourists’ understanding of low-carbon tour packages in Taiwan, their purchase intention, and willingness to pay. The following results were revealed. First, international tourists in Taiwan exhibited a certain degree of understanding of low-carbon tour packages (M = 3.79). Second, the understanding of low-carbon tour packages significantly influenced purchase intention; particularly, tourists’ views about food and accommodation effectively predicted their purchase intention. Third, 34.5% of international tourists in Taiwan were willing to pay 5% more to purchase low-carbon tour packages, and 32.3% of international tourists in Taiwan were willing to pay 10% more to purchase low-carbon tour packages. That the results of this study can serve as a reference for the government and travel agencies to design and determine prices for low-carbon tour packages.